The evaluation criteria as a fundamental part of didactic programming - Polo Martínez, Ignacio (Avances en Supervisión Educativa, 2011)
While the Organic Law 2 / 2006 of 3 May (BOE 05/04/2006), Education, Article 6, defined as the set of curriculum objectives, core competencies, content, teaching methods and evaluation criteria, these past have been falling gradually relegated to second or third place in the planning of teaching. The teacher thinks he knows exactly what grade has a student, however, that sometimes what is being assessed to students significantly far from what makes a mandatory curriculum. Usually begins to decline in the realization of the objectives of the curriculum from subject-area. From here begins a step concretions through training objectives that sometimes cause a desvirtualización the requirements of the assessment criteria of the official curriculum. This article attempts to value the evaluation criteria and minimum requirements as a fundamental part of the programming current faculty teaching.